Konsep Penyelesaian Sengketa Harta Warisan Dalam Hukum Islam - Khaled, Muhammad (Al-Mizan, 2023)
This article discusses the concept of resolving inheritance disputes in the context of Islamic law. The settlement of inheritance disputes involves clear provisions in Islam, including the division of inheritance based on family relationships and the role of mediation. This article elaborates on the concept of inheritance, heirs' rights, and the role of mediation in resolving inheritance disputes. In this context, village officials knowledgeable in religious matters play a crucial role as mediators in handling inheritance disputes. The aim of this article is to provide a better understanding of how the resolution of inheritance disputes can be conducted within the framework of Islamic law, considering legal and humanitarian aspects. The research method used in this study is qualitative, as it can explain the phenomena of the studied community based on several literature studies. The research findings reveal that in Islamic law, the division of inheritance has clear provisions, regulating different proportions for each heir based on family relations. Mediation plays a key role in settling inheritance disputes, allowing disputing parties to reach a fair agreement and prevent further conflicts. Village officials competent in religious matters can act as mediators in this mediation process, with the ability to calm emotions, listen carefully, and facilitate discussions towards solutions in line with Islamic law. With this approach, the resolution of inheritance disputes in Islamic law can become more effective and in line with religious principles.